2021
DOI: 10.21603/2074-9414-2021-2-333-348
|View full text |Cite
|
Sign up to set email alerts
|

Food and Feed Protein Preparations from Peas and Chickpeas: Production, Properties, Application

Abstract: Introduction. New legume-based protein preparations are an excellent alternative to polymers of animal origin and can eliminate the protein deficiency in the diet of humans and animals. In this respect, the raw material base of common leguminous crops has to be thoroughly analyzed in order to develop new technological schemes for novel protein formulations. Study objects and methods. The present research compared modern trends in the production, properties, and safety of food and feed protein preparation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 43 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…It has been shown that dietary fiber from pea grain shells after preliminary fermentation can be used for the production of dairy and bakery products. Bioconversion of pea grain shells for the production of fodder additives [6] and biofuels [7][8] holds certain promise. The processing of shell biopolymers (starch, cellulose, pectin) can produce functional packaging films and coatings with added value [7].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that dietary fiber from pea grain shells after preliminary fermentation can be used for the production of dairy and bakery products. Bioconversion of pea grain shells for the production of fodder additives [6] and biofuels [7][8] holds certain promise. The processing of shell biopolymers (starch, cellulose, pectin) can produce functional packaging films and coatings with added value [7].…”
Section: Introductionmentioning
confidence: 99%